2023
DOI: 10.1002/advs.202203757
|View full text |Cite
|
Sign up to set email alerts
|

Mutant KRAS Drives Immune Evasion by Sensitizing Cytotoxic T‐Cells to Activation‐Induced Cell Death in Colorectal Cancer

Abstract: The roles of oncogenic KRAS in tumor immune evasion remain poorly understood. Here, mutant KRAS is identified as a key driver of tumor immune evasion in colorectal cancer (CRC). In human CRC specimens, a significant reduction in cytotoxic CD8 + T-cell tumor infiltration is found in patients with mutant versus wild type KRAS. This phenomenon is confirmed by preclinical models of CRC, and further study showed KRAS mutant tumors exhibited poor response to anti-PD-1 and adoptive T-cell therapies. Mechanistic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…These pathways can point that T-cell response and antigen presentation were reduced in KRAS-positive tissues, as described by Liu et al. ( 89 ).…”
Section: Discussionmentioning
confidence: 58%
“…These pathways can point that T-cell response and antigen presentation were reduced in KRAS-positive tissues, as described by Liu et al. ( 89 ).…”
Section: Discussionmentioning
confidence: 58%
“…In fact, immune checkpoints alone are not sufficient to predict the efficiency of the immunotherapy due to a highly complex immune tumor microenvironment, which could be generalized by a cancer immunity cycle (87). Several studies have suggested integrating multiple biomarkers to predict the immune response, including tumor-infiltrating lymphocytes, mutational b u r d e n , i m m u n e g e n e s i g n a t u r e s , a n d m u l t i p l e x immunohistochemistry (88,89). TIDE is a reliable surrogate biomarker that could accurately predict immune checkpoint blockade (ICB) response by measuring the tumor immune escape, and it even performed better than PD-L1 expression in melanoma; that is, a higher TIDE score is associated with worse ICB response and worse patient survival under anti-PD1 and anti-CTLA4 therapies (90).…”
Section: Discussionmentioning
confidence: 99%
“…We also explored MSI and LRHG signatures during the research process. The common mutation in GC is KRAS, which plays an important role in immunotherapy for solid tumors and colorectal cancer 46 , 47 . Whether there is a relationship between KRAS mutations and immunotherapy in GC patients remains unproven.…”
Section: Discussionmentioning
confidence: 99%